The Role of Managerial Ability in the Relationship between Managerial Ownership and Tax Avoidance - Masripah, Masripah; Widyastuti, Shinta; Dwi Handayani, Devi; Putri Faradhisa, Jasmine (Dinasti Publisher, 2024)
This research was conducted to empirically test the influence of managerial ownership and managerial ability on tax avoidance, as well as the role of managerial ability in the relationship between managerial ownership and tax avoidance. This research uses secondary data in the form of company financial and annual reports. The sampling technique uses purposive sampling with the population being manufacturing companies in various industrial sectors listed on the Indonesia Stock Exchange in 2019 - 2023. This research uses regression analysis with panel data from a sample of 430 firm years. The data analysis technique for this research uses model selection tests, classical assumption tests, and hypothesis tests which are processed using STATA version 17. The research results show that managerial ownership has a negative effect on tax avoidance. Meanwhile, managerial ability has no effect on tax avoidance. Managerial ability also does not moderate the effect of managerial ownership on tax avoidance.